Self Disclosure of Gen Z Employees of JNT Buduran Branch in Facing Quarter Crisis Of Life: Self Disclosure Gen Z Karyawan JNT Cabang Buduran Dalam Menghadapi Quarter Crisis Of Life - Hayyu, Hayyu Fallah Al Fattah; Asy’ari, Nur Aini Shofiya (Universitas Muhammadiyah Sidoarjo, 2025)
The phenomenon of Quarter Life Crisis (QLC) has become a significant challenge for Generation Z (Gen Z) employees, particularly those working in lower-middle sectors, such as couriers at J&T Buduran Branch. This crisis is characterized by confusion, career uncertainty, and emotional pressure, which can affect their performance and well-being. One strategy to cope with this condition is through self-disclosure. This study aims to analyze the role of self-disclosure using the Johari Window theory approach in helping Gen Z employees at J&T Buduran deal with QLC. This research employs a descriptive qualitative method with a case study approach. Data were collected through semi-structured interviews, observation, and documentation involving five employees at J&T Buduran Branch aged 20–27 years. Data analysis was conducted using Miles and Huberman’s interactive model, with validation through source and method triangulation. The results show that most employees feel comfortable sharing their experiences with trusted colleagues (open area). However, some choose to hide their feelings for fear of being perceived as weak (hidden area). Several employees became aware of their shortcomings through feedback from supervisors or coworkers (blind area), while work challenges helped them discover previously unknown potentials (unknown area). In conclusion, self-disclosure plays an important role in managing the emotional pressures caused by QLC. Therefore, it is recommended that companies create a more supportive work environment to encourage employee self-disclosure. Future research may explore other factors influencing QLC, such as work culture and organizational policies